A Retrospective Examination of Rodrigo Duterte’s Populist Politics in the Philippines (2016-2022) Applying Taggart’s Framework - Espiritu, Rovil (Indonesian Journal of Social Science Research, 2025)
This study carries out a retrospective analysis of the central elements of Dutertismo—Rodrigo Duterte's brand of populism during his presidency in the Philippines from 2016 to 2022. Utilizing Paul Taggart's framework to analyze relevant literature, the paper discusses how Duterte leveraged populism to consolidate power, framing entities like the Liberal Party, the media, the Roman Catholic Church, and drug users as adversaries of the State. It highlights Duterte's responses to international scrutiny from bodies like the International Criminal Court and human rights organizations, which he accused of infringing on Philippine sovereignty. The research further explores Duterte’s portrayal of the drug issue as a national crisis, his manipulation of public opinion through surveys and social media, and his implementation of vague policies and agenda. Additionally, the paper analyzes the chameleonic nature of Duterte’s politics, evidenced by his alliances with traditionally liberal institutions such as the Philippine National Police and the Armed Forces, along with his interactions with the Communist Left. This analysis offers a deeper understanding how Duterte's leadership style has shaped the country's political dynamics and how it resonates with or differs from other populist movements globally.